Investigation of red blood cell and platelet indices in adult dogs suffered from myxomatous mitral valve disease with and without pulmonary hypertension - Tangmahakul, Nattawan; Orton, E. Christopher; Surachetpong, Sirilak Disatian (Frontiers in Veterinary Science, 2023)
Background Pulmonary hypertension (PH) is a common complication of cardiopulmonary disease. In dogs, PH commonly occurs secondary to myxomatous mitral valve disease (MMVD). Red blood cell and platelet indices including mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), mean platelet volume (MPV) and platelet distribution width (PDW), have previously been found to be indicators for predicting and prognosing PH in humans. Therefore, this study aimed to investigate whether these indices are associated with MMVD and/or PH in dogs. Methods Two hundred and forty-six dogs were retrospectively recruited for the study and classified into 4 groups: normal (n = 49), MMVD (n =102), PH (n =17), MMVD+PH (n =78). A sub-analysis was performed in dogs with MMVD without evidence of PH according to stage B1 (n =20), stage B2 (n =15), stage C (n =67). The data are expressed as median (interquartile range). Results and discussion No significant differences (p < 0.05) were found in MCV, RDW and MPV among all groups (normal, MMVD, PH and MMVD+PH). However, decreases in MCH and MCHC were found in MMVD [22.40 (20.90-23.50) pg and 35.25 (33.08-36.90) g/dL], MMVD+PH [22.25 (20.85-23.98) pg and 35.65 (33.30-37.33) g/dL] and PH groups [21.20 (20.60-22.20) pg and 33.80 (32.75-35.70) g/dL] compared to the normal dogs [24.29 (23.55-24.90) pg and 38.20 (37.50-39.05) g/dL] (p < 0.001). Decreases in PDW were found in dogs in the MMVD+PH [15.10 (14.98-15.30) %] groups compared to dogs in the normal group [15.30 (15.10-15.50) %] (p = 0.004). Sub-analysis of MMVD dogs without PH showed a decrease in MCH in dogs with stage B2 MMVD [21.00 (20.50-22.90) pg] and stage C MMVD [22.40 (20.90-23.20) pg] compared to normal dogs [24.29 (23.55-24.90) pg] (p < 0.001). MCHC of dogs with stage B1 [36.55 (33.53-37.78) g/dL] (p = 0.004), B2 [32.90 (32.00-35.00) g/dL] (p < 0.001) and C MMVD [35.30 (33.30-36.80) g/dL] (p < 0.001) were lower than those of normal dogs [38.20 (37.50-39.05) g/dL]. PDW in the stage C MMVD group [15.10 (15.00-15.30) %] was reduced compared to the normal group [15.30 (15.10-15.50) %] (p = 0.042) and the stage B1 MMVD group [15.35 (15.23-15.68) %] (p = 0.002). MCH, MCHC and PDW were negatively correlated with the left atrial and left ventricular size. Conclusion Decreases in MCH and MCHC are related to MMVD, precapillary PH and postcapillary PH while PDW are associated with MMVD severity but not with the presence of PH.